An Andrographis paniculata Burm. Nees extract standardized for three main Andrographolides prevents house dust mite-induced airway inflammation, remodeling, and hyperreactivity by regulating Th1/Th2 gene expression in mice - Sulaiman, Ibrahim; Okwuofu, Emmanuel Oshiogwe; Mohtarrudin, Norhafizah; Lim, Jonathan Chee Woei; Stanslas, Johnson (Elsevier Ireland, 2024)
Ethnopharmacological relevance: Andrographis paniculata Burm. Nees (AP) is an herb used traditionally in Indian and Chinese traditional medicine for the treatment of various inflammatory and respiratory tract diseases. However, the anti-inflammatory potential of standardized Andrographis paniculata 50% ethanol extract (APEE50) in the murine model of asthma has not been investigated. Aim of the study: This study aimed to evaluate the protective anti-inflammatory potential and better understand the underlying mechanism of action of APEE50 in a clinically-relevant mouse asthma model. Thereafter, develop the ethanolic extract of AP as a supplement for asthma prophylaxis. Materials and method: APEE50 was prepared and standardized for AGP, NAG, and DDAG using a high-performance liquid chromatography system. Asthma was induced according to a 14-day house dust mite (HDM) induction protocol. The prophylactic potential of APEE50 (50 mg/kg – 200 mg/kg) was determined by assessing cardinal asthma features, which included BALF leukocyte and differential cell count, BALF cytokine assay, histology, gene expression, and airway hyperreactivity study. Results: APEE50 significantly inhibited HDM-induced airway eosinophilia and neutrophilia. In addition to decreased levels of IL-4, IL-5, IL-13, and eotaxin in bronchoalveolar fluid, APEE50 abrogated HDM-induced airway mucus over-secretion and airway hyper-responsiveness. Administration of APEE50 downregulated HDM-induced upregulation of the oxidative stress enzyme Duox1 (dual oxidase 1) and marginally induced Nfe2l2 (nuclear factor erythroid 2-related factor 2) gene expressions. Similarly, Th2-related (Serpinb2, Clca3a1, Il4 and Il13) and Muc5ac gene expression were significantly downregulated. Conclusion: Prophylactic administration of APEE50 prevented the progression of HDM-induced asthmatic responses by down-regulating Th2 cytokine gene expression and oxidative stress level.